2021
DOI: 10.2105/ajph.2020.305999
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Use and Adult Cigarette Smoking Cessation: A Meta-Analysis

Abstract: Objectives. To determine the association between e-cigarette use and smoking cessation. Methods. We searched PubMed, Web of Science Core Collection, and EMBASE and computed the association of e-cigarette use with quitting cigarettes using random effects meta-analyses. Results. We identified 64 papers (55 observational studies and 9 randomized clinical trials [RCTs]). In observational studies of all adult smokers (odds ratio [OR] = 0.947; 95% confidence interval [CI] = 0.772, 1.160) and smokers motivated to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
175
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(192 citation statements)
references
References 89 publications
6
175
0
11
Order By: Relevance
“…Population evidence regarding the effectiveness of using NVPs to quit smoking is mixed; however, there is growing evidence from randomized trials and observational studies that NVPs can be helpful in facilitating quit smoking attempts, reductions in cigarette consumption, and smoking cessation. 8 , 12 , 25–31 While the evidence of effectiveness for cessation has not been found in other studies, 25 , 32 , 33 it does indicate stronger effects when NVPs are used to quit smoking (vs. use for other reasons) when a certain type of device used (e.g., tank-based system, salt-based e-liquid), and when used more frequently (e.g., daily). 27 , 33–37 …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Population evidence regarding the effectiveness of using NVPs to quit smoking is mixed; however, there is growing evidence from randomized trials and observational studies that NVPs can be helpful in facilitating quit smoking attempts, reductions in cigarette consumption, and smoking cessation. 8 , 12 , 25–31 While the evidence of effectiveness for cessation has not been found in other studies, 25 , 32 , 33 it does indicate stronger effects when NVPs are used to quit smoking (vs. use for other reasons) when a certain type of device used (e.g., tank-based system, salt-based e-liquid), and when used more frequently (e.g., daily). 27 , 33–37 …”
Section: Discussionmentioning
confidence: 88%
“… 8 , 12 , 25–31 While the evidence of effectiveness for cessation has not been found in other studies, 25 , 32 , 33 it does indicate stronger effects when NVPs are used to quit smoking (vs. use for other reasons) when a certain type of device used (e.g., tank-based system, salt-based e-liquid), and when used more frequently (e.g., daily). 27 , 33–37 …”
Section: Discussionmentioning
confidence: 88%
“…Importantly, many of the early trials used first‐generation cig‐a‐likes that deliver relatively low doses of nicotine, possibly influencing quit rates. Supporting the idea that nicotine dose is an important determinant of success in smoking cessation, quitting rates in the population as a whole are higher when later‐generation e‐cigarettes with higher power such as tank‐style devices are used compared with first‐generation devices 90 and when e‐cigarettes are used more frequently 90,91 . The only trial to date using modern pod devices was a harm reduction study using 59 mg/mL nicotine pods 92 .…”
Section: Potential To Aid Smoking Cessation/support Harm Reductionmentioning
confidence: 99%
“…Data from US surveys have found an association between the increase in e‐cigarette use and smoking cessation rates 98 and higher prevalence of a recent successful quit attempt among exclusive e‐cigarette users compared with users of other or no noncigarette tobacco products use 99 . A recent meta‐analysis of population‐based studies confirmed increased quitting with daily but decreased quitting with nondaily e‐cigarette use 91 . These findings should be interpreted in the light of the previous mentioned limitations in relation to the large heterogeneity of the available e‐cigarette devices and nicotine concentrations, as well as limitations associated with the study design (eg, cross‐sectional design not allowing assessment of causality).…”
Section: Potential To Aid Smoking Cessation/support Harm Reductionmentioning
confidence: 99%
“…In the past decade, public health effort has resulted in significant reduction in the prevalence of tobacco smoking. However, there is a dramatic rise in the consumption of alternative products that delivers nicotine, such as e-cigarettes 4 . Menthol is the most popular and preferred e-cigarette flavor among young users 5 .…”
Section: Introductionmentioning
confidence: 99%